Hidrolisis Protein Teripang Hitam (Holothuria edulis) Menggunakan Bromelin Kasar dari Batang Nanas (Ananas comocus L): Protein Hydrolysis of Black Sea Cucumber (Holothuria edulis) Using Crude Bromelain from Pineapple Stem (Ananas comocus L) - Fakhrija Sahraini; Abd. Rahman Razak; Syaiful Bahri; Hardi Ys. (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Black sea cucumber is one type of sea cucumber whose protein content is quite high at 74-82%, not yet widely used by the community as a source of protein. One way to use it is to process the protein into a protein hydrolyzate using the bromelain enzyme which was isolated from pineapple stems. This study aims to determine the concentration of the bromelain enzyme extract and the optimum hydrolysis time to the value of the hydrolysis degree of the hydrolyzate of black sea cucumber protein. Protein hydrolysates are produced by variations of the crude bromelain concentration of 9%, 10%, 11%, and 12% (v/v) and hydrolysis time of 120, 180, 240, and 300 minutes. The results showed that the optimum degree of hydrolysis was obtained with the use of bromelain extract with a concentration of 12% with a value of 11.43% and a hydrolysis time of 240 minutes with a value of 19.17%.